First-Line A Direct Aspiration First-Pass Technique vs. First-Line Stent Retriever for Acute Ischemic Stroke Therapy: A Meta-Analysis - Hsieh, Kevin Li-Chun; Chuang, Kai-I; Weng, Hsu-Huei; Cheng, Sho-Jen; Chiang, Yu; Chen, Cheng-Yu (Frontiers in Neurology, 2018)
Backround Recent trials have proved the efficacy of mechanical thrombectomy over medical treatment for patients with acute ischemic stroke, with the balance of equivalent rates of adverse events. Stent retrievers were applied predominantly in most trials; however, the role of other thrombectomy devices has not been well validated. A direct aspiration first-pass technique (ADAPT) is proposed to be a faster thrombectomy technique than the stent retriever technique. This meta-analysis investigated and compared the efficacy and adverse events of first-line ADAPT with those of first-line stent retrievers in patients with acute ischemic stroke. Methods A structured search was conducted comprehensively. A total of 1623 papers were found, and 4 articles were included in our meta-analysis. The Critical Appraisal Skills Programme tools were applied to evaluate the quality of studies. The primary outcome was defined as the proportion of patients with the Thrombolysis in Cerebral Ischemia (TICI) scale of 2b/3 at the end of all procedures. Secondary outcomes were the proportion of patients with functional independence (modified Rankin scale of 0-2) at the third month, the proportion of patients with the Thrombolysis in Cerebral Ischemia (TICI) scale of 2b/3 by primary chosen device, and the proportion of patients who received rescue therapies. Safety outcomes were the symptomatic intracranial hemorrhage (sICH) rate and the mortality rate within 3 months. Results One randomized controlled trial, one prospective cohort study, and two retrospective cohort studies were included. No significant difference between these 2 strategies of management were observed in the primary outcome (TICI scale at the end of all procedures, odds ratio [OR] = 0.78), two secondary outcomes (functional independence at the third month, OR = 1.16; TICI scale by primary chosen device, OR = 1.25), and all safety outcomes (sICH rate, OR = 1.56; mortality rate, OR = 0.91). The proportion of patients who received rescue therapies was higher in the first-line ADAPT group (OR = 0.64). Conclusions Among first-line thrombectomy devices for patients with ischemic stroke, ADAPT with the latest thrombosuction system was as efficient and safe as stent retrievers.